WEALTH TAX WITHIN EUROPE IN THE CONTEXT OF A POSSIBLE IMPLEMENTATION IN ROMANIA– THE EXISTING WEALTH TAX AND ITS DECLINE IN EUROPE - LUMINIŢA RISTEA; ADINA TRANDAFIR (Annals of the University of Petrosani: Economics, 2010)
The purpose of this paper is to focus our attention on the conceptualbasis upon which the wealth tax system may be implemented in Romania taking intoconsideration former and actual presence of wealth tax within Europe. The idea of increasingthe taxable basis based on imposing the wealth constitutes one of the most important debatetopics on the agenda of the Romanian Parliament and Government and also within specialists’theoretical approaches. The vast range of such approaches and further solutions is to beanalysed in the global context of direct taxation in Europe and worldwide and particularlyrelevant for the complexity of the problem is the evolution of wealth tax during the last decadesand also the very important context of moving corporate main offices in countries with moreadvantageous systems of taxation.